Development and Validation of a New HPTLC Method for Determination of Protopine in Accelerated Solvent Extract of Fumaria vaillantii Loisel - A. Rajopadhye, Anagha; S. Upadhye, Anuradha (Asian Journal of Chemistry, 2012)
A new, simple and accurate HPTLC method is developed using ICH guidelines for the determination of protopine in methanolic whole plant extract of Fumaria vaillantii Loisel. Accelerated solvent extraction (ASE) as an alternative to convention techniques was also explored for the rapid extraction. Chromatographic separation was performed on silica gel 60 F254 HPTLC plates in the mobile phase of methyl ethyl ketone:ethyl acetate: formic acid (5:3:2, v/v/v) and the plates were scanned densitometrically at 293 nm (lmax of protopine). The amount of protopine was found in range 1.29-1.41 and 1.47-1.54 mg/g in Soxhlet and ASE 80 ºC extracted plant sample, respectively. The HPTLC method was validated in terms of sensitivity, accuracy, precision and reproducibility. Accelerated solvent extraction method has higher extraction efficiency in less time as compared to conventional Soxhlet extraction. Rapid and reproducible method is useful for routine analysis of protopine and quality control of F. vaillantii.